Safety in an unsafe world: Perceptions of security among Syrian refugees in Turkey - Narli, Nilüfer (International review of victimology, 2025)
This paper draws on 380 face-to-face interviews with Syrian refugees living in Istanbul. It considers their perceptions of risk and safety in Istanbul. It does so by drawing on the criminological literature on fear of crime to relate the lived experiences of refugees to their perceptions of security in an unsafe world, namely the problems they have experienced on their journey to Istanbul; the extent to which they are well established in Türkiye; their contact with the police and attitude toward the police and other public services; their social, physiological, and psychological vulnerability; and their relationship with and reliance upon community and state. Overall, we conclude that revising the concepts used for explaining fear of crime in a conventional context successfully accounts for variations between refugees living in an unsafe world.